The Nature Of Social Commitments Required To Promote Corporate Social Responsibility In The Platinum Mining Sector In Zimbabwe - MUNONEKA, SITHOLE; OBERT, SIFILE; MTHOMBENI , ADMIRE (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2024)
The study sought to establish the nature of social commitments required to promote corporate social responsibility (CSR) in the mining sector in Zimbabwe. The study adopted the mixed method approach rooted in the pragmatism paradigm and a cross-sectional descriptive survey design. Stratified random sampling and purposive sampling were used. An interview guide and a questionnaire were used as research instruments. The sample size was 181 respondents, representing 2 400 artisanal platinum miners in Mashonaland West Province, calculated using the Krejcie and Morgan formula. SPSS version 24 was used for analysing quantitative data, while NVivo was used for the analysis of qualitative data. The study indicates that adoption of the Extractive Industries Transparency Initiative (EITI) transparency in the form of enhanced disclosures, led to effective CSR in the mining sector, benchmarking to lobal Reporting leads to effective CSR and consistent adherence and adoption of the International Standards Organisation (ISO). Results show that implementing the EITI could promote accountability to society and lead to effective CSR. The study recommends that the Mines and Minerals Act or the Indigenisation and Economic Empowerment Act should include a provision requiring any mining firm operating in Zimbabwe to support local communities through CSR.